From single pioneers to complex pro- and eukaryotic microbial networks in soils along a glacier forefield chronosequence in continental Antarctica - Amen, Rahma; Ganzert, Lars; Friedl, Thomas; Rybalka, Nataliya; Wagner, Dirk (Frontiers in Microbiology, 2025)
IntroductionIn the extremely dry and oligotrophic soils of East Antarctica, where low temperatures and humidity result in minimal biological turnover rates, extracellular DNA (eDNA) can persist over extended timescales. Differentiating between sequences from living, potentially active cells (intracellular DNA, or iDNA) and those from ancient, non-living organisms (eDNA) is crucial for accurately assessing the current microbial community and understanding historical microbial dynamics.MethodsThis study was conducted along a chronosequence in the Larsemann Hills, East Antarctica, where soil samples were collected from sites at varying distances from the glacier. By employing DNA separation methods, we distinguished iDNA, which represents living cells, from eDNA derived from dead organisms. High-throughput sequencing was used to characterize bacterial and eukaryotic communities across different successional stages.ResultsThe DNA separation approach revealed distinct bacterial and eukaryotic community structures along the glacier transect. Actinobacteria were consistently abundant across all sites, while other phyla such as Chloroflexi, Gemmatimonadetes, and Proteobacteria thrived in extreme, nutrient-poor environments. Early successional stages were characterized by the simultaneous colonization of green algae Trebouxiophyceae and cryophilic fungi, alongside nitrogen-fixing bacteria, which contributed to initial soil development. The study also identified three distinct modes of microbial distribution, reflecting varying degrees of activity and adaptability.DiscussionOur findings provide new insights into microbial dynamics in extreme habitats and propose new hypotheses for microbial colonization in newly exposed soils. Moreover, they contribute to the ongoing debate in microbial ecology regarding the viability of dormant or dead cells and emphasize the need for refining DNA-based methods and exploring functional pathways to deepen our understanding of microbial succession in polar regions.